Analisis Wacana Kritis Dampak Tarif Resiprokal AS di KompasTV - Wellyana, Nur; Patriantoro, Patriantoro (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the discourse on the impact of reciprocal tariffs imposed by the United States on Indonesia as presented in KompasTV news reports using Teun A. Van Dijk's Critical Discourse Analysis (CDA) approach. This analysis focuses on the macro, superstructure, and micro structures of discourse to reveal how KompasTV represents the issues and ideologies underlying the news report. The US reciprocal tariffs have a significant impact on Indonesia-US trade relations, affecting export performance and national industrial strategies in response to the tariff policy. The mass media, especially television as a visual and audio medium, plays an important role in shaping public opinion through news framing patterns that can support or oppose the policy. This study explores how KompasTV's use of language and narrative shapes public perception and drives socio-political dynamics in news coverage. The results of this study provide a comprehensive understanding of the role of the media in shaping public opinion on international economic issues and serve as an important reference for policymakers and further research in the field of critical discourse analysis.